Early education and child care : a sociocultural approach - Edwards, Susan (Australia : Pademelon press, 2014)
how sociocultural theory can be used in practice
Includes bibliographical reference and index.
Keywords: Early childhood education -- Australia; Child development -- Australia; Child care -- Australia